PENGARUH TIME BUDGET PRESSURE DAN FEE AUDIT TERHADAP KUALITAS AUDIT PADA KANTOR AKUNTAN PUBLIK (KAP) DI DAERAH JAKARTA SELATAN - Yulientinah, Dewi Selviani; Arthia, Haya Nazihah Putri (Universitas Logistik dan Bisnis Internasional, 2025)
In the face of increasingly fierce business competition and various problems in Indonesia, the role of public accounting services is very important with high demands for relevance and reliability. Auditors from the Public Accounting Firm (KAP) are responsible for providing reliable assurance of financial statements, but audit quality is still a concern due to incidents of fraud. This study aims to analyze the effect of time budget pressure and audit fees on audit quality. The problems discussed include the effect of time budget pressure on audit quality, the effect of audit fees on audit quality, and the effect of both simultaneously. This study uses primary data from questionnaires distributed to 70 auditors at 10 KAPs in South Jakarta. The sample selection was selected using purposive sampling technique. The hypothesis was tested with a two-tailed test. Analysis techniques include descriptive statistics, validity test, reliability test, normality test, Pearson product moment correlation analysis, multiple correlation analysis, multiple linear regression analysis, t test, F test, and coefficient of determination analysis. The test results show that partially, time budget pressure has a significant effect on audit quality, while audit fees have no significant effect. The F test results show that time budget pressure and audit fees simultaneously have no significant effect on audit quality, with a coefficient of determination of 7%.